Педагогічні принципи підвищення загальної культури студентів-економістів - Орел, Вікторія Вікторівна (НТУ "ХПІ", 2012)
The article is devoted to the question of transfer to students of the certain set of knowledge of social and economic and psychological features of different trades; about conditions of a correct choice of one of them; education of the positive attitude to motivated professional intentions in which basis comprehension of social and economic needs of a society by them and the psychophysical opportunities lays.
Keywords: технократизм; вища освіта; соціокультурна проблема